TO THE CONCEPT OF OPTIMAL INDEBTEDNESS IN COMPONENTSOF INTELLIGENT TRANSPORT SYSTEMS - Bartošová, V.; Majerčák, J. (Science and Transport Progress, 2005)
ITS are based on three key principles: information, communication and integration. The functionality of ITS must be provided by all levels: by administration, transport operators and transport users. It seems to be sine qua non for the positive synergy and expected economical effects.